EFSA review of Maximum Residue Limits for halquinol in pig tissues as set by JECFA. Issue 7 (6th July 2021) - ,; de Lourdes Bastos, Maria; Bories, Georges; Brantom, Paul; Galobart, Jaume; Gropp, Jürgen; Marcon, Francesca; Pizzo, Fabiola; Villa, Roberto Edoardo; Vettori, Maria Vittoria
Abstract: The European Commission requested the European Food Safety Authority (EFSA) to review the evaluation of halquinol by the 85 th and 88 th meetings of the Joint FAO/WHO Expert Committee on Food Additives (JECFA) and to assess any other relevant scientific information in order to establish whether there is ground for any food safety concerns about the maximum residues levels (MRLs) recommended by JECFA. In several countries halquinol is used as a veterinary drug in pigs and poultry to enhance growth performance while this is prohibited in the European Union. JECFA derived an Acceptable daily intake (ADI) of 0‐0.2 mg/kg body weight, based on histopathological changes associated with an increase in mean absolute and relative kidney weights seen in a 1‐year chronic toxicity study conducted in rats and has recommended MRLs for halquinol of 500, 9000, 40 and 350 μg/kg in pigs liver, kidney, muscle and skin+fat, respectively. Overall, EFSA considers that the MRLs for halquinol proposed by JECFA are sufficiently low to ensure the safety of European consumers when exposed to foodstuffs from halquinol treated pigs. However, due to some limitations and uncertainties in the toxicological database available, EFSA is not in the position to confirm the ADI of 0‐0.2 mg/kg bw, as set by JECFA.